Determination of the Volume of Water for Suppressing the Thermal Decomposition of Forest Combustibles; Journal of Engineering Physics and Thermophysics; Vol. 90, iss. 4 - Volkov R. S. Roman Sergeevich; Zhdanova A. O. Alena Olegovna; Kuznetsov G. V. Geny Vladimirovich; Strizhak P. A. Pavel Alexandrovich (2017, 2017)
Title screen